Analyzing Factors Affecting Farmers' Decisions in Applying Organic Vegetable Farming - Kris Indra Sanjaya; Tinjung Mary Prihtanti (Indonesian Journal of Agricultural Research, 2018)
Farming with organic systems is one of the important efforts to support sustainable agriculture. The purpose of this study is to determine the factors that influence farmers to decide to implement organic vegetable farming. This research was conducted in June 2018 until September 2018 in Selongisor Hamlet, Batur Village, Getasan Subdistrict, Semarang Regency. Taking this research was conducted on a non-probability sampling with purposive sampling technique with the required criteria, namely respondents who cultivated in multicultural/intercropping. Samples taken were 60 samples consisting of 30 samples for each system both organic and inorganic. The research analysis used logistic regression, where the independent variables analyzed included age, education level, farm area, farm income, cosmopolitan farmers. The results showed the influence of land area, farmer's income and cosmopolitan farmer's decision making in cultivating organic vegetables.